Investigating the role of Adrenomedullin signalling during zebrafish development - Parker, Nathan (2025)
The cardiovascular system is the first functional organ system to develop in vertebrates. It links all other organ systems and is essential for normal development. The blood-brain barrier (BBB) is a highly selective semi-permeable interface between blood vessels and the brain. How the selective permeability of the BBB is established during development remains poorly understood. Here, I have identified that in zebrafish, Adrenomedullin signalling via Calcrl/Ramp2 promotes the normal development of the blood vascular network. Genetic variants in CALCRL and RAMP2 and their regulatory elements are associated with predisposition to human diseases including stroke and coronary artery disease. In mice, embryonic lethality prevents detailed characterisation of the function of Adrenomedullin signalling during development. Furthermore, the roles of Adrenomedullin signalling have been disputed, with some studies reporting defective lymphatic specification and others reporting reduced vascular integrity. Therefore, understanding the mechanisms by which Adrenomedullin signalling regulates zebrafish cardiovascular development may help to improve understanding of the role of Adrenomedullin signalling during cardiovascular development. Ultimately, this may aid development of effective therapeutics targeting human cardiovascular diseases.